2007
DOI: 10.1002/jhet.5570440434
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective cyclodehydration of ortho‐hydroxy acetyl aryloxyketones to benzofuran

Abstract: ortho‐Hydroxy acetyl benzofuran derivatives have been synthesized in a regioselective cyclodehydration of aryloxyketones obtained from β‐resacetophenone and α‐halo ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Ortho-hydroxy acetyl benzofurans (1a-1d) [13], were condensed with different aryl aldehydes in 1 % ethanolic sodium hydroxide to give corresponding chalcones (2a-2l). Though such a low concentration of alkali was used, there was no evidence of formation of flavanones, which was contradictory to the reports in literature which indicated that low concentration of alkali favoured ring closure J. M. Patel and S. S. Soman Vol 45 whereas high concentration of alkali favoured ring fission [14].…”
Section: Resultsmentioning
confidence: 99%
“…Ortho-hydroxy acetyl benzofurans (1a-1d) [13], were condensed with different aryl aldehydes in 1 % ethanolic sodium hydroxide to give corresponding chalcones (2a-2l). Though such a low concentration of alkali was used, there was no evidence of formation of flavanones, which was contradictory to the reports in literature which indicated that low concentration of alkali favoured ring closure J. M. Patel and S. S. Soman Vol 45 whereas high concentration of alkali favoured ring fission [14].…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectrum of compound 4 showed singlets at δ 5.65 and δ 12.00 ppm, both corresponding to one proton each for H-6 and 5-OH, respectively. However, the angular isomer 4 could not be studied further because of the poor yields of 1-(4-hydroxy-3-methylbenzofuran-5-yl)ethanone 2 [13]. Posner reaction of 5-hydroxy-3-methylfuro[3,2-g]chromen-7-one 3 with hydroxylamine hydrochloride using pyridine gave 1-(6-hydroxy-3-methylbenzofuran-5-yl)ethanone oxime 5 as the major product; but when the reaction was carried out in methanol the major product obtained was 5-methylfuro [2',3':4,5]benzo-[1,2-d]isoxazole-3-yl)acetic acid 6, as shown in Scheme 1.…”
mentioning
confidence: 98%
“…As shown in Scheme 1, 1-(6-hydroxy-3-methylbenzofuran-5-yl)ethanone 1 [13] and 1-(4-hydroxy-3-methyl-benzofuran-5-yl)ethanone 2 [13] on reaction with pulverized sodium and diethyl carbonate [14] gave new linear 5-hydroxy-3-methylfuro[3,2-g]chromen-7-one 3 and angular 7-hydroxy-3-methylfuro[3,2-g]chromen-7-one 4 isomers, respectively. The structures of both compounds were confirmed by their 1 H NMR spectra.…”
mentioning
confidence: 99%
“…18 Among this prolific family of heterocycles, the 3-aryl-4-hydroxybenzo furan framework can be found in a series of pharmacologically relevant structures. [19][20][21][22] Recently, 3-aryl-4hydroxybenzofurans have been identified as the AMP-activated protein kinase and the ribosomal protein kinase inhibitors for the treatment and chemoprevention of cancer, diabetes, aging-related diseases or processes, or neurodegenerative diseases, 20 prostacyclin receptor inhibitors for cardiovascular diseases therapy and prevention. 22 In addition, Schiff bases are an important class of compounds in medicinal and pharmaceutical field that show vast biological applications.…”
mentioning
confidence: 99%